Ideologi Penggunaan Istilah-Istilah Covid-19 di Berita Online: Analisis Wacana Kritis Model Norman Fairclough - Akhmad Samsuri; Widyatmike Gede Mulawarman; Yusak Hudiyono (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This study aims to describe the structure of the text (text dimension), discourse practice (dimension of social practice), and sociocultural practice (sociocultural dimension) against the use of COVID-19 terms in online news. The research method used is qualitative descriptive The critical discourse analysis approach Norman Fairclough used to find the depth of meaning of news texts containing COVID-19 terms. The term data about COVID-19 is taken from three websites, namely Bisnis.com, Kompas.com, and Liputan6.com. Based on the results of the analysis, it was concluded that, first, the text structure in the form of advisories, information, and education about events (events) increasing COVID-19 cases and policy actions taken by the government to reduce COVID-19 cases. Second, discourse practices include the identity of the government and society. Third, the dimension of sociocultural practice indicates policies that impact: (a) the marginalization of society, (b) social dominance, and (c) social wrong because the policies implemented are not to the conditions of society. The results of this study are expected to provide a correct understanding of the use of COVID-19 terms in online news so that the public can be more critical in reading news in online media.